The COVID-19 wave was already here: High seroprevalence of SARS-CoV-2 antibodies among staff and students in a Cameroon University - Andrillene Laure Deutou Wondeu; Beatrice Metchum Talom; Giulia Linardos; Barnes Tanetsop Ngoumo; Aïchatou Bello; Aurele Marc Ndassi Soufo; Aimé Cesaire Momo; Christian Doll; Alaric Talom Tamuedjoun; Jules-Roger Kiuate; Giulia Cappelli; Cristina Russo; et al. (AOSIS, 2023)
Background: Seroprevalence studies, to estimate the proportion of people that has been infected by SARS-CoV-2 are importance in African countries, where incidence is among the lowest in the world. Objective: This study aimed at evaluating the exposure to SARS-CoV-2 within a university setting of Cameroon. Methods: A cross-sectional study performed in December 2020 - December 2021, among students and staffs of the Evangelical University of Cameroon. COVID-19 antigen rapid detection test (RDT) was performed using Standard Q Biosensor, and one year after SARS-CoV-2 antibody-test was performed within the same population using RDT and chemiluminescence immunoassay (CLIA). Results: 106 participants were enrolled (80% students), female sex was the most represented. Positivity to SARS-CoV-2 was 0.0% based on antigen RDTs. The seroprevalence of SARSCoV- 2 antibodies was estimated at 73.6% (95% CI. 64.5-81.0) for IgG and 1.9% (95% CI. 0.2-6.8) for IgM/IgG with RDTs, and 91.9% (95% CI. 84.7-96.4) for anti-nucleocapsid with CLIA. 95.3% (101) reported having developed at least one of the known COVID-19 symptoms (cough and headache being the most common). 90.3% (28) of people who experienced at least one of these symptoms developed IgG antibodies. 40.6% (43) of participants took natural herbs, whereas 55.7% (59) took conventional drugs. The most used herb was Zingiber officinale, while the most used drugs were antibiotics. Conclusion: In this Cameroonian University community, SARS-CoV-2 seroprevalence is high, with a greater detection using advanced serological assays. This indicates a wide viral exposure, and the need to adequate control measures especially for those experiencing any related COVID-19 symptoms.